Konflik Norma Kewenangan Pembuatan Akta yang Berkaitan dengan Pertanahan: Conflict of Norms for the Authority to Make Deeds Relating to Land - Andreasari, Letizia Dessy (WARKAT, 2022)
The authority of Notaries and Land Deed Officials in making land deeds is still conflicting (conflict of norms). Land deeds made by Notaries based on Article 15 paragraph (2) UUJN were rejected by the National Land Agency (BPN) on the grounds that the deeds were under the authority of the Land Deed Making Official. BPN insists that the authority to make land deeds is the authority of Land Deed Making Officials based on Government Regulation Number 37 of 1998 concerning Position Regulations for Land Deed Making Officials which are implementing regulations of Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations. On the other hand, if it is based on the provisions of the Notary Position Regulations (PJN) according to Article 1 Staatblad 1860 Number 3, the official appointed to make deeds of transfer and assignment of land rights is a Notary. These two things make the notary's authority and the PPAT's authority in making deeds related to land become disharmonious and ultimately result in conflicting norms. Resolving the legal disharmony in regulating the authority of Notaries and PPATs in making land deeds can be carried out based on the principle of lex superiori derogate lex inferiori as in legal theory (Preference Theory). There needs to be harmonization of these two norms by creating a PPAT Law so that the positions of Notaries and PPATs are equal and also that PPAT deed products become authentic because they fulfill the elements of Article 1868 BW, namely the form of the deed is regulated in the Law.